Unveiling the impact of improvement methodologies on employee engagement: Insights from central European companies - Urban, Wieslaw (Technological and Economic Development of Economy, 2025)
Improvement methodologies (IMs) consist of many components; however, employee engagement (EE) is particularly important in bottom-up initiated process improvement. This study aims to investigate EE with reference to IMs used by companies. EE measurement constructs focused on process improvement has been developed and verified as reliable. This study examines a sample of 380 medium- and large-sized companies. The ANOVA procedure proves that: (1) IMs support EE in companies, and (2) the absence of IMs leads to lower EE. However, support for EE is specific and does not primarily concern issues directly related to process improvement. This study also discovers the multi-use of IMs by companies. IMs such as Lean, strongly focused on EE by their assumptions, only moderately support EE in companies. The study found no exceptionally effective IM which allows for the easy gain of EE in the investigated companies’ current state of implementation. The results imply that companies are approximately halfway towards the effective use of IMs. They should rethink the use of IMs, transform their leadership style, and better motivate employees to engage in bottom-up process improvement, which is indispensable. First published online 18 November 2024